Is there an optimum level of financial activity? - Michael Graff (ETH Zurich, KOF Swiss Economic Institute, 2005)
This paper addresses the notion of an optimum level of financial activity that is contingent on a country's general level of development. Referring to threshold regressions and a bootstrap test for structural shift of the finance regressor in a growth equation, it is shown that countries gain less from a given level of financial activity, if the latter fails to keep up with or exceeds what would follow from a balanced expansion path. The paper contributes to the literature on the finance-growth nexus in providing empirical support for the notion of balanced financial development with a development specific optimum level of financial activity.
Keywords: O11; P17; C11; 330; Optimum financial activity; Bayesian statistics; bootstrapping; Finanzsektor; Entwicklung; Wirtschaftswachstum; Bayes-Statistik; Bootstrap-Verfahren